Redes de apoio às famílias de dependentes de álcool e outras drogas: uma interface com as políticas públicas intersetoriais - Goulart, Daniela Cristina Soares [UNESP] (2014)
This paper discusses about the dependence of alcohol and other drugs, specifically its implications on the family context, introducing theoretical and legal elements, in addition to the considerations stated by the social subjects accessed in this research. It shows a brief history of psychoactive substance dependence, conceptualizing families and, then, presents the preamble upon thesupport and solidarity networks destined to families under drug addiction treatment. It emphasizes the necessity of enhancing the attention that should be drawn to the families of those addicted to alcohol and other drugs in small towns, where there are actions related to public policies regarding mental health, alcohol and other drugs in a disarticulated and incipient manner. Therefore, a field research was conducted with social workers and coordinators from different social service programs, in the city of Piumhi, state of Minas Gerais, with the purpose of analyzing the existing support network provided to the families of users, through interfacing with intersectoral public policies on this location. The results aim at defending the importance of reinforcing families through the foundation of social policiesundertaken by the public initiative, with consistent actions and programs which meet all their needs, permeated by totality, respect towards its plurality and diversity, regardless of how they have been set, in order to face issues related to the dependence of alcohol and other drugs